Traditional Medicinal Plants as an Element of Thematic Garden Landscapeat SMAN 1 Pondidaha, Konawe Selatan, Sulawesi Tenggara - Faslih, Arman; Al Ikhsan, Ainussalbi; M, Agung Yodha; Wahyuni, Wahyuni (UI Scholars Hub, 2017)
Knowledge of traditional medicinal plants among teenagers are quite low, that caused by the information is very limited as well as the difficulty of obtaining real-life examples of traditional medicinal plants. Those inspired us to cooperate with SMAN 1 Pondidaha District Konawe (Sulawesi Tenggara) in an effort to provide solutions to these problems. SMAN 1 Pondidaha has vacant land large enough. Through IbM program (Ipteks bagi Masyarakat, science and technology for the People) Ministry or Research and Technology and Higher Education, we made thematic landscape in SMAN 1 Pondidaha locations using traditional medicinal plants as fillers garden or park. The method was conducted on the survey and measurement, search species of plants data that suitable with the design, preparation of location and soil for planting of medicinal plants, labeling and maintenance. The results showed there are 6 types of medicinal plants are required for the design, namely 1) medicinal plants such as jarak (Jatropha curcas), jarak merah (J. gossypifolia), jarak tintir (J. multifida) and bougainvillea (Bougenvillea spectabilis), 2) medicinal plants and aesthetics, for example kembang sepatu (Hisbiscus rosasinensis), kembang nusa endah (Mussaenda philippia), tapak dara (Catharanthus roseus), 3) Barrier crops include gandaruso (Justisia gandarusso), Ashoka (Saraca asoca), teh- tehan (Duranti erecta), kroton (Codiacum variegatum), mangkokan (Notophanax scutellarium), 4) Vertical garden Plants include lavender (Lavendula angustifolia), selasih (Ocium sp.), pancawarna (Hydrongea macrophylla), cabe hias (Solanum pseudo-capsicum), 5) Shade plants, for example pule (Alstonia scholaris), ketapang (Terminalia catappa), kelapa (Cocus nucifera), kamboja (Plumeria sp.), beringin (Ficus benjamina) and 6) Cover crops such as bunga kriminil (Althenantera amoena), rumput gajah (Pennisetum purpureum), rumput jepang (Zoysia japonica). These plants are used by the people as a remedy for various diseases.